Assessment of Drinking Water Quality of Madhyapur-Thimi and Study of Antibiotic Sensitivity against Bacterial Isolates - Jayana, Bina Laxmi; Prasai, Tista; Singh, Anjana; Yami, Kayo Devi (Nepal Journal of Science and Technology, 2010)
The study was undertaken to assess the existing status of drinking water quality of Madhyapur-Thimi. A total of 105 water samples comprising 50 (47.61%) wells, 45 (42.82%) tap water and 10 (9.52%) stone spouts were randomly collected. The physicochemical and microbiological parameters were analyzed following standard technique. The pH (1.9%), conductivity (34.28%) and turbidity (16.19%) of water samples had crossed the permissible guideline values as prescribed by WHO and national standard. All samples contained nitrate values within the WHO permissible value as well as national standard but hardness (2%), chloride (2.85%), iron (26.66%), ammonia (11.42%), and arsenic content (1.90%) crossed the WHO guideline value but none of the water samples crossed the national standard for arsenic. Arsenic having 0.025mg/l (25ppb) was detected from two well water samples, Makanani well and Ajimanani well. Total coliform count showed 64.76% of samples crossed the WHO guideline values. Eleven different kinds of enteric bacteria were isolated from different sources, Enterobacter spp. being the predominant. Isolates were subjected for antibiotic susceptibility pattern using ten antibiotics. Among total isolates, resistance was directed to 79.5% Erythromycin, 62.67% Penicillin G, 61.9% Amoxycillin, 34.5% Ampicillin, 21.1% Tetracycline, 15.4% Ceftriaxone, 14.7% Amikacin, 14.7% Cephotaxine, 5.6% Chlorophenical and 5.6% Ofloxacin respectively. Key words: Coliform; Enteric bacteria; Permissible value; Physicochemical; Antibiotic resistance DOI: 10.3126/njst.v10i0.2955 Nepal Journal of Science and Technology Vol. 10, 2009 Page: 167-172